565 Current data regarding homeostasis of tissues oxygenation in pathophysiological and therapeutic circumstances (Balneo and PRM Research Journal, 2024)
Abstract: Oxygen is essential for cellular respiration and energy production. Tissue oxygenation refers to delivering oxygen to cells throughout the body. Microcirculation brings blood through small sanguine vessels to maintain the cells' supply of nutrients and oxygen. Optimal tissue oxygenation and microcirculation are essential for maintaining healthy tissue. Conversely, poor oxygenation can cause tissue damage, impair wound healing, and increase infection risk. Several factors can affect tissue oxygenation and microcirculation, including age, lifestyle factors (such as smoking and stress), and underlying medical conditions (such as diabetes and high blood pressure). To improve tissue oxygenation and microcirculation, individuals can engage in healthy lifestyle habits such as regular exercise, healthy eating, stress management, and avoiding smoking. Tissue oxygenation can also be looked therapeutic, given that topical and cosmetic treatments such as massage, pelotherapy, hydrotherapy, moisturizers, and certain skin care products can help promote healthy microcirculation at the somatic level. In the scientific literature, the focus is on hypoxia rather than tissue oxygenation. This article proposes a paradigm shift and emphasizes the homeostatic importance of microcirculation and tissue oxygenation in pathophysiological and therapeutic circumstances. The systematic review of the data from the last 2 years (2021-2022) and the meta-analysis performed on tissue oxygenation will contribute to the practical approach to the pathology circumscribed to tissue oxygenation.